A função social da propriedade da terra no processo de desapropriação da Fazenda Annoni (1972-1993) - Dickel, Simone Lopes (2016)
The Annoni Farm, located in the northern Rio Grande do Sul region, belonging to the municipalities of Pontão and Sarandi, got space in the news in 1985. It became known when it was target of the largest land occupation in Brazil until then, coordinated by the newly created Landless Movement (MST) at the beginning of the democratic period. In the year of 2015, the occupation, which helped to make the farm on of the symbols of the agrarian reform, with the participation of more than 1,500 families of landless, completed its 30th anniversary. However, before that, a major conflict - and little known around the dispossession of Annoni - occurred since the beginning of the 1970s, involving expropriated (Annoni family) and the Union. The aim of this dissertation is to understand the history of the Annoni Farm based on its expropriation process, showing how it evolved in the history of the farm, which can not be done without taking into account the regional and national historical contexts, considering that the process went on for decades in wich there have been significant transformations, which are the years 1970, 1980 and 1990, which are subject of this study. Remaining part of the large regional latifundia named Sarandi Fazenda, which was constant scene of conflicts over land by different subjects, Annoni had its expropriation decree issued in 1972, however, little is known about the judicial process of dispossession. The conflict in justice, which has given this lawsuit the title of one of the largest civil cases seen in Brazil until then, runs through the decades of 1970, 1980 and 1990 and extends to almost the present day. Goes through different contexts, changes in legislation and even through the conception of the struggle for agrarian reform, and the occupation of 1985 rushed the release of land for theo ones who are camping there, but not reaching, however, the end of the legal dispute over the ownership of Annoni , which continues, although in other respects.